Effectiveness of Planned Teaching Program on Knowledge Regarding Preparation of Nursing Process among Nursing Students - Pandya, Rachana; Patel, Vruti; Patel, Khushbu; Patel, Hitisha; Patel, Maitree (International Journal of Psychosocial Rehabilitation, 2020)
Background: The nursing process is considered an appropriate method for explaining the essence of nursing, its scientific bases, creativeness, critical thinking process, and problem-solving in professional practice. The nursing process is characterized as the global concept that is being taught and implemented worldwide. Different global organizations like WHO & ICN (International Council for Nurses) also acknowledged the use of the nursing process as the central-integral concept among nursing professionals. The developed and detailed standardized nursing care plan consists of the nursing diagnosis, definition, etiological or related causative factors that contribute to the patient’s condition, recording its pattern, desired optimum outcomes, and nursing care orders, which are nursing interventions. Objectives: To assess the knowledge of nursing students regarding the preparation of the nursing process. To prepare and administer planned teaching programs for nursing students on the preparation of the nursing process. To evaluate the effectiveness of a planned teaching program for nursing students on the preparation of the nursing process. Material and Methods: A quantitative research approach with a pre-experimental, one-group pretest-posttest design is used for the study, and data is collected from 100 samples of nursing students using a non-probability purposive sampling technique. A planned teaching program regarding preparations of the nursing process with 10 standardized care plan preparations was implemented for all students. Results: With regard to the pretest and posttest assessments, they indicate that there is a drastic increase in the knowledge level of nursing students after providing a planned teaching program. The planned teaching program was effective in improving knowledge among nursing students regarding the preparation of standardized nursing processes.